Ceviche-Natural Preservative: Possibility of Microbiota Survival and Effect on L. monocytogenes - Arkadiusz Józef Zakrzewski; Wioleta Chajęcka-Wierzchowska; Anna Zadernowska (Foods, 2022)
Ceviche is a marinated raw fish dish ready for consumption; it is a part of the cuisine of various countries on the Pacific coast and its preparation may differ among them. Although the process uses the traditional method of food preservation by lowering the pH, the exposure time is very limited, so the aim of the study was to determine the viability of bacteria often isolated from fish after the process of preparing traditional ceviche. For this purpose, the traditional plate method and flow cytometry were used, and for pathogenic L. monocytogenes strains, the influence of stress during the preparation of the dish on the pathogenic potential was determined. The study showed that the highest percentage of viable cells was observed in the case of L. monocytogenes and remained at the level of 98.54%, slightly less for L. innocua, 96.93%. For the remaining species the reduction did not exceed 10%, for E. faecalis it was 92.76%, for S. liqefaciens 91.44%, H. alvei 93.68%. In addition, the study of the antibacterial properties of individual ingredients showed that habanero and coriander did not show any bactericidal effect, while for onions the amount of live cells was 99.11%, and for lime juice 97.26%, Additionally, the study of changes in virulence, antibiotic resistance and gene expression showed that the stress during the preparation of ceviche has different effects depending on the strain and may cause virulence potential increase, levofloxacin and daptomycin minimum inhibiotory concentration increase and some crucial virulence gene expression induction; therefore, it is important to take care of the quality of the products used to prepare the ceviche and accurate pretreatment.